Continuing use of antithrombotic medications for patients with bleeding gastroduodenal ulcer requiring endoscopic hemostasis: a case–control study. (2nd September 2017) - Kawasaki, Keisuke; Nakamura, Shotaro; Kurahara, Koichi; Nagasue, Tomohiro; Yanai, Shunichi; Harada, Akira; Yaita, Hiroki; Fuchigami, Tadahiko; Matsumoto, Takayuki
Abstract: Objective: The aim of this study was to compare clinical characteristics and outcomes of bleeding gastroduodenal ulcer between patients taking antithrombotic medications and those not taking antithrombotic medications. Methods: We performed a case–control study of 346 patients with endoscopically verified bleeding gastroduodenal ulcer, which included 173 cases taking antithrombotic medications throughout peri-bleeding period and 173 age- and sex-matched controls not taking antithrombotic medications. Results: The cases showed less frequent Helicobacter pylori ( H. pylori ) infections (45.1% versus 60.7%, p = .005), more frequent duodenal location (31.8% versus 19.1%, p = .009), and more frequent rebleeding (13.9% versus 5.8%, p = .02) than the controls. Multivariate analysis revealed that duodenal location (odds ratio [OR] 3.01, 95% confidence interval [CI] 1.37–6.65) and use of antithrombotic medications (OR 2.47, 95% CI 1.13–5.77) were independent factors for rebleeding. However, there were no differences in clinical outcomes, including final successful endoscopic hemostasis, need for surgical intervention, and mortality between cases and controls. Thromboembolic events did not occur in any cases and controls during the periendoscopic period. Conclusions: Low prevalence of H. pylori infection, frequent duodenal location, and high rebleeding rate are characteristics of patients with bleeding gastroduodenal ulcer under antithrombotic medications. Continuation of antithrombotic medications can be accepted for bleeding gastroduodenal ulcer.